The question of the asyndetic complex sentence in the Ukrainian and Russian linguistics (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is devoted to the analysis of working-out the question of the asyndetic complex sentence in the Ukrainian and Russian linguistics, it is done a try to compare the aspects and the patterns of the research of the given topic. It is determined the tendencies of the further development of studying the asyndetic complex sentence.
Keywords: asyndetic complex sentence; asyndetic connection; complex sentence; compound sentenc